Yeast from Epiphyte of Avocadoes to Control Colletotrichum gloesporioides Causing Antrachnose Disease - Anton Muhibuddin; Siti Fadhilah; Antok Wahyu Sektiono; Umi Kulsum Nur Qomariyah; Mazidatul Faizah; Ambar Susanti; Sri Nurhatika (SAINTEKBU, 2018)
Anthracnose disease caused by Colletotrichum gloesporioides fungi is an important disease in avocado fruit during storage. An effective, cheap, and non-poisoned control method was required during storage to minimize chemical pesticide residues. This observation was aimed to select yeast with antagonistic ability from avocado epiphyte. Selected yeasts then tested their antagonist ability versus Colletotrichum gloesporioides, the fungi causing anthracnose disease, in vitro. Based on visual observation, microscopically and macroscopically, knowing that there were 3 yeast species isolated from green-long avocado variety i.e.: Candida sp., Filobasidium sp., and Cryptococcus sp., and then from mega gagauan avocado variety i.e.: Pichia sp., Candida sp., Cryptococcus sp., and Metschnikowia sp. The most antagonist yeast was Cryptococcus sp, which isolated from green long avocado. Keyword: Yeast, antagonist, storage, avocado, anthracnose